The influence of organic urban morphologies on opportunities for home-based businesses within inner-city districts in Hanoi, Vietnam. Issue 6 (2nd November 2019) - Thai, Ha Minh Hai; Stevens, Quentin; Rogers, Judy
ABSTRACT: To a typical family in Hanoi, their house is not solely their home, but a valuable basis for their livelihood: a home-based business. This paper investigates the spatial impact of the city's dominant built form characterized by organic urban morphology and building typology on home-based economic activities. Space Syntax is adopted to examine the proximity from these homes to the local main streets, which provides a pool of customers. Findings show that home-based economic opportunities are spatially distributed and sorted. The paper provides an evidence-based understanding of the economic performance of informal urbanism, and the potential impacts of urban design and planning decisions on individuals' and cities' economic well-being.